Still Looking for a Development Blueprint. - Veith, Richard H.; Armour, Phillip G. (Communications of the ACM, 2014)
A letter to the editor is presented in response to Phillip G. Armour’s article "Estimation Is Not Evil" about software development (SD) environments, the Waterfall SD method, and vendor management which appears in the January 2014 issue.